Evolution of multifunctional land use systems in mountain areas in Italy - Raffaello Giannini; Antonio Gabbrielli (Italian Journal of Agronomy)
This work presents an analysis of the evolution of human activity in Italian mountain areas, as regards to agricultural and forestry land use. Due to the large area occupied by woodlands, the analysis focusses on the relationships between man and forests. Three closely linked systems have been analysed: agriculture, pasturage and silviculture, which are primary resources used to satisfy human food and energy requirements. From the point of view of the landscape, crops and forest products remain separate entities, even if a link to pasturage remains. Two typical cases of multifunctional systems have been described. The first is related to the alpine area, and the second one concerns the Apennines. The documentation on land use in mountain areas underlines the deep-seated relationships that have developed over time between human activity and the forest. Until the middle of the 20th century, the agriculture-forestry systems were integrated into field, pasture and woodlands in which the portion dedicated to pasture was dominant. Today, forests play a primary role since they offer economic advantages and when correctly managed they can provide a diversified flow of services.